Treatment of Central Diabetes Insipidus with Intranasal Desmopressin and Intravenous Vasopressin Following Pituitary Macroadenoma Resection: A Systematic Review and Case Report - Machado, Luiz Guilherme; Moretto, Guilherme; Rosa, Tiago Gonçalves; Silva, Leonardo Carmo Kawakame da; Addison, John; Luz, José Leonardo; Zenteno, Luís Felipe de La Cerda (Brazilian Journal of Case Reports, 2026)
Central diabetes insipidus (CDI) is a relatively common neuroendocrine complication following transsphenoidal resection of pituitary macroadenomas, with an incidence ranging from 20% to 35%. This study aimed to evaluate recent literature on the management of postoperative CDI with desmopressin and to report a clinical case characterized by an atypical course and delayed therapeutic response. A systematic review was conducted according to the PRISMA 2020 guidelines, including studies published between 2020 and 2025. Twenty articles met the eligibility criteria, comprising a total of 2,964 patients. The mean incidence of postoperative CDI was 27.1%, of which 73% were transient cases. Desmopressin demonstrated a response rate of 92% (including all routes of administration), with an average time to polyuria control of 3.9 hours. Treatment-related hyponatremia occurred in 6.8% of cases. The case report describes a 45-year-old female patient with severe CDI, prolonged clinical course, and the need for intravenous vasopressin for 12 days before stabilization with intranasal desmopressin. The findings confirm that desmopressin is an effective and safe treatment; however, delayed responses may occur following extensive surgery for invasive tumors (particularly those with clival invasion) or in patients who develop immediate postoperative local complications that interfere with drug absorption. Individualized management and rigorous monitoring are essential to prevent hydroelectrolytic complications (such as iatrogenic hyponatremia resulting from rapid correction) and to optimize outcomes. Based on the available evidence and clinical experience, a structured therapeutic escalation protocol is proposed.